Influence of Tool Pin Profiles on Aluminium Alloy A356 and Ceramic-Based Nanocomposites for Light Weight Structures by Friction Stir Processing - L. Karthick; Mruthunjaya M.; Srinivas. S.; Prasanna Venkatesh R.; Naveen Kumar Gurajala; Meghavath Mothilal; Hari Banda (Advances in Materials Science and Engineering)
In this research, the main aim is to focus the enhancement of aluminium-based metal matrix composites for improving the attributes of light weight metals, aerospace structures and other tailor blank material properties. By this way, the friction stir processing (FSP) was the suited alternate technique to enhancing the mechanical attributes and superior microstructural amendment in the processed MMCs. Therefore, this study investigates the dispersion of ceramic-based strengthening particles of chromium oxide (Cr2O3) in the aluminium base matrix of A356 alloy. During the processing, the different tool pin sizes having the conical threaded tool pin profiles. Similarly, the tool spinning speed and tool travel speed also varied while in FSP. Before the processing, the A356 alloy was prepared by the grooved surfaces for packing the chromium oxide particles to compose the aluminium metal matrix composites. The tensile strength and hardness was employed to carry out from the friction stir processed A356 alloy with influencing of Cr2O3. The maximum occurred tensile processing parameters are 1500 rpm of spinning speed, 6 mm of tool pin sizes and 90 mm/min of tool travel speed. Similarly, the maximum obtained hardness processing parameter are 2000 rpm of spinning speed, 5 mm of tool pin sizes and 90 mm/min of tool travel speed. A scanning electron microscope was utilized to investigate the dispersed Cr2O3 in the A356 alloy for confirming the refinement grains in the nugget zones of FSPed A356 alloy. The increased grain boundary by the influence of different tool pin sizes was the major reason to produces the better mechanical properties in the processed A356/Cr2O3.